It`s not all about power: a systematic review and meta-analysis comparing sex-based differences in kicking biomechanics in soccer - Boyne, M.; Simms, C.; van Dyk, N.; Farrell, G.; Farrell, E.; McHugh, C.; Wall, J.; Mockler, D.; Wilson, F. (Sports Biomechanics, 2021)
Kicking is fundamental in many field-based sports. Most studies investigating kicking performance have been conducted with male athletes, resulting in a dearth of specific data to inform coaching of this skill in female players. This systematic review aimed to compare kicking biomechanics in male and female athletes in field-based sports. As per PRISMA guidelines, articles were retrieved from searches across five online databases. Studies investigating kicking biomechanics in field-based athletes of both sexes were eligible for inclusion. Articles were screened using Covidence and data extracted based on STROBE recommendations. The review included 23 studies, featuring 455 soccer players. Male athletes produced significantly greater ball velocities and linear velocities of the ankle, foot, and toe than females. Males had greater ankle plantarflexion angles than females at ball strike, while females used larger trunk flexion ranges than males. Hip and knee torques and ball-to-foot velocity ratios were greater in men than women. Skilled players generated power using tension arcs; a technique not seen in novices. Skill level within sex may have a greater influence on kicking performance than differences between the sexes. This review highlights the need for further research investigating kicking performance in both sexes across the spectrum of sports.